ALLERGIC CONTACT DERMATITIS WITH AN UNUSUAL CONFIGURATION AFTER PREOPERATIVE POVIDONE-IODINE DISINFECTION. A CLINICAL CASE - Yoanna Velevska-Vatova; Filka Georgieva (Peytchinski Publishing, 2023)
Contact dermatitis is an inflammatory skin reaction resulting from skin contact with exogenous substances that act as allergens and/or irritants. Epicutaneous testing is the gold standard for diagnosing allergic contact dermatitis and differentiating it from irritant contact dermatitis. We present a clinical case of allergic contact dermatitis after preoperative povidone-iodine disinfection.